Zeal without burnout : seven keys to lifelong ministry of sustainable sacrifice - Ash, Christopher, 1953- ([Place of publication not identified] : The Good Book Company, 2016)
Christopher Ash's wisdom has been distilled into this short, accessible book, in which he reveals a neglected biblical truth and seven keys that flow from it. Understood properly, and built into our lives as Christians who are zealous to serve the Lord, they will serve to protect us from burnout, and keep us working for God's kingdom and glory.
Stories from the edge -- A crucial distinction -- A neglected truth -- Seven keys -- We need Sabbath rests -- We need friends -- We need inward renewal -- A warning -- An encouragement -- A delight.
Keywords: Pastoral theology; Pastoral theology